Konvergensi Media dan Teknologi: Implikasinya terhadap Komunikasi Pemasaran Pariwisata - Setiyorini, Heri Puspito Diyah (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
This paper would give a conceptual discussion of the media convergence, technology acceptance model, andÂ Â  its implication on tourism marketing communication. Media convergence is the integration of multiple media, particularly conventional media with the new media. Conventional media such as a printed, audio, and audio-visual media are now integrated by the Internet technology. Thus, the information can be accessed through the personal devices. This notion affects to the way people use their leisure times, as well as, the industry do the marketing activities for tourism. Since the length of stay of tourists is decreasing, so the technology intent to assist these activities to the tourist. Hence, the paper would also discuss the tendency of the short-break tourists and the tourism business players in using the technology and its implication to the marketing communication.